50 great myths of human sexuality - Schwartz, Pepper; Kempner, Martha (Chichester, West Sussex, UK Malden, MA : Wiley-Blackwell, 2015)
There exists a wide range of misconceptions concerning human sexuality, many of which are certified by self-appointed "experts" and passed on as the absolute truth; some of which are even taught in schools. Some of these misconceptions are so misleading as to be dangerous while others can cause needless worry and anxiety.
50 Great Myths of Human Sexuality seeks to dispel commonly accepted myths and misunderstandings surrounding human sexuality. Authors Schwartz and Kempner provide an enlightening, fascinating and challenging book that covers the fifty areas they believe individuals must understand to have a safe, pleasurable and healthy sex life. Encompassing heterosexual and same-sex relationships where possible, these include myths surrounding pre-marital sex, masturbation, sexual diseases, fantasy, pornography, contraception, and understanding emotions such as jealousy, body image insecurity, passionate love and sexual aggression and how they affect sexual health and happiness.
Based on their collective years of experience working in the field of human sexuality, the authors provide an enlightening, fascinating and challenging book for students learning about human sexuality, and an engaging introduction for general readers interested in questions about the human behavior, sexuality, and gender diversity.--Book Jacket.
Body parts: who has what and how it works -- Orientation and identity: who we are and who we want -- Sexual stats: Who has sex? How often? How hot? -- Performance: lights, camera, orgasm -- Conception and contraception: illusions and delusions -- STIs and protection: the risks of romance -- Relationships: dating and desire -- When sex is unhealthy: sex and trouble -- The not-so-private side of sex: sex, society, and the law.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Sex -- Miscellanea; Sex customs -- Miscellanea; Man-woman relationships -- Miscellanea; SOCIAL SCIENCE / Anthropology / Cultural; Man-woman relationships; Sex; Sex customs; Miscellanea; Electronic books; Electronic books